2022
DOI: 10.3389/fneur.2022.838456
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Endovascular Rescue Therapy on the Clinical and Radiological Outcome After Aneurysmal Subarachnoid Hemorrhage: A Safe and Effective Treatment Option for Hemodynamically Relevant Vasospasm?

Abstract: ObjectiveCerebral vasospasm (CVS) represents one of the multiple contributors to delayed cerebral ischemia (DCI) in patients with aneurysmal subarachnoid hemorrhage (aSAH). Especially the management of CVS, refractory to medical treatment, is a challenging task during the acute phase after aSAH. Endovascular rescue therapies (ERT), such as medical and mechanical dilation, are possible treatment options on an individual basis. However, data about the influence on the patients' functional outcomes are limited. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…To date, there are no larger randomized controlled trials investigating the impacts of endovascular treatment for vasospasm. However, several recent retrospective studies confirmed that early endovascular vasospasm treatment improves functional outcomes and may be effective against the development of DCI [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no larger randomized controlled trials investigating the impacts of endovascular treatment for vasospasm. However, several recent retrospective studies confirmed that early endovascular vasospasm treatment improves functional outcomes and may be effective against the development of DCI [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hingegen mangelt es an prospektiven randomisierten Studienergebnissen zur Wirksamkeit von endovaskulären Spasmustherapien (EST); diese werden jedoch u. a. in Leitlinien der amerikanischen Fachgesellschaften zur additiven Behandlung von ZVS explizit erwähnt [5]. Unzweifelhaft werden angiografische Interventionen mit lokaler Applikation von gefäßerweiternden Medikamenten und auch die Ballonangioplastie (BA) in sehr vielen Institutionen auch in Mitteleuropa und speziell Deutschland durchgeführt [3,7,8].…”
Section: Einführungunclassified
“…In contrast, there is a lack of prospective randomized trial results on the efficacy of endovascular vasospasm treatments (EVT); however, these are explicitly mentioned in, among others, guidelines of the American professional societies on additive treatment of CVS [5]. There is no doubt that angiographic interventions with topical application of vascular vasodilators as well as balloon angioplasty (BA) are performed in a very large number of institutions, including in Central Europe and especially Germany [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, a clear recommendation is lacking here as for endovascular spasm therapy (EST). This is also due to the fact that to date there is no evidence of a positive effect on clinical outcome even though there are indications of an additional benefit of EST based on numerous at times complicated studies including metaanalyses [17][18][19][20][21]. Thus, there is also currently a lack of consensusbased guidelines regarding EST even though they are broadly implemented and include the intraarterial administration of medication (also in the form of continuous therapy with microcatheters) and mechanical vascular dilation (balloon angioplasty [BA], dilation by means of other instruments, e. g. stent retrievers, stenting).…”
Section: Introductionmentioning
confidence: 99%
“…Jedoch fehlt hierfür ebenso eine klare Empfehlung wie für endovaskuläre Spasmustherapien (EST). Auch dies ist dem Umstand geschuldet, dass bislang keine Evidenzen für einen positiven Einfluss auf den klinischen Ausgang vorliegen, obgleich sich Hinweise auf einen zusätzlichen Nutzen von EST aus zahlreichen, teils aufwändig konzipierten Studien unter Berücksichtigung auch von Metaanalysen ergeben [17][18][19][20][21]. So mangelt es also auch aktuell an konsentierten Leitlinien für EST, welche jedoch unzweifelhaft ubiquitär durchgeführt werden und dabei intraarterielle Medikamentengaben (auch als Dauertherapien mit Mikrokathetern) und mechanische Gefäßerweiterungen (Ballonangioplastie [BA], Dilatationen durch andere Instrumente wie z.…”
Section: Introductionunclassified